Private Supplementary Tutoring in Turkey Recent Evidence on Its Various Aspects - Aysit Tansel; Fatma Bircan (Turkish Economic Association, 2007)
This paper first describes the educational system in Turkey and the two national examinations for advancing upper levels of schooling which give raise to the demand for private tutoring called dersane in Turkish. Second, the evolution of the Private tutoring Centers (PTC) are described and compared with the high schools in the country. Third, geographical distribution of the PTC, general high schools and the proportion of high school age population are compared over the provinces to give an idea about special equity issues. Other topics addressed include gender and PTC students, disruption of mainstream education, determinants of the demand for services of the PTCs, cost of PTCs and evidence on the effectiveness of PTCs
Keywords: I20; I21; I22; 330; Private Tutoring; Education; Demand for Education; Bildungswesen; Bildungsverhalten; Bildungsinvestition; Privatschule; Studium; Türkei